UPAYA MASYARAKAT LOKAL DALAM MENJAGA KEAMANAN DAN KENYAMANAN WISATAWAN DI DESA ADAT UBUD (Studi Tindakan Sosial dalam Pariwisata) - I Wayan Cahya Suputera; I Gst. Agung Oka Mahagangga (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2016)
Ubud traditional village is a tourist area which is located in Gianyar regency. If the tourist want know the culture of Bali they must come to Ubud. However, many issues and problems arise associated with security and tourists comfortness. Based on it, this research was conducted to analyze the Local Community Efforts in Maintaining Security and Tourists Comfortness in Ubud Traditional Village.The method used in this research is a research method with qualitative descriptive analysis technique to analyze the efforts and actions of local communities. Sources of data derived from primary data and secondary data. Data collecting technique using in-depth interviews, observation and study of literatures. Determination of informants from local communities in this study using purposive sampling technique. This study is limited by the analysis of the social action theories and coordination systems. The results of this research obtained that local community efforts in maintaining security is the assignment of trepti unit who participate in keeping any tourism activities..